Optimal Prevention for Multiple Risks. Issue 3 (23rd October 2015) - Courbage, Christophe; Loubergé, Henri; Peter, Richard
Abstract : This article analyzes optimal prevention in a situation of multiple, possibly correlated risks. We focus on probability reduction (self‐protection) so that correlation becomes endogenous. If prevention concerns only one risk, introducing a second exogenous risk increases the level of prevention expenditures, even if correlation is negative. If prevention expenditures may be invested for both risks, a substitution effect arises. Under nonincreasing returns on self‐protection, we find that increased dependence increases aggregate prevention expenditures, but not necessarily prevention expenditures for each risk due to differences in prevention efficiency. Similar results are found when considering changes in the severity of losses. Consequently, the comparative statics emphasize global effects versus allocation effects. Our results have strong policy implications, considering the numerous mandatory safety measures introduced by governments over the past years.